(untitled) (Colloquia Comparativa Litterarum, 2025)
Lubomir Guentchev is a Bulgarian writer whose work was discovered in 1999. By 1930, he had conceived poems in Bulgarian, then, between 1949 and 1955, plays including one, which he transposed into French (Théurgie). He translated Bulgarian Symbolist poets into French (Peyo Kr. Yavorov, Nikolai Liliev and Teodor Trayanov, among others), and numerous French and German authors into Bulgarian. He also composed several collections of poetry in French. To what extent did this bilingualism foster in him a paradoxical phenomenon of self-restraint imposed by the circumstances of the time? What were its motives, goals and scope?